Hubungan Antara Screen Time dengan Angka Kejadian Miopia Pada Anak Sebelum dan Setelah Masa Pandemi Covid-19 : Sebuah Tinjauan Pustaka - Anugrahsari, Santi; Shania Audrianisa; Cahya Virgin Septyany; Appy, Enjeline Grecielya; Rohy, Charlos Ivanly Jusuf (Jurnal MedScientiae, 2024)
The COVID-19 pandemic policies, outdoor activity restrictions, and distance learning have significantly impacted the occurrence of myopia in children. These changes are associated with increased screen time, decreased outdoor activities, and insufficient sleep duration, indicating potential long-term effects on myopia prevalence and development. This literature review utilizes articles from research journal databases searched through the internet. The internet databases used include Google Scholar and PubMed, using keywords: "Children," "Epidemiology," "Risk Factor," and "Myopia." Inclusion criteria for this literature are English articles, published within the last 10 years, and research publication types. Exclusion criteria include duplications and articles with only abstracts or without full text. The combined findings of these studies consistently demonstrate that school-age myopia is influenced by genetic and environmental factors, with screen time, near work, and urban residence being significant risk factors. The protective role of outdoor activities against myopia is evident in various geographic regions. The COVID-19 pandemic has exacerbated this issue, emphasizing the need for interventions focused on reducing screen time and increasing outdoor activities to manage and prevent myopia progression.